Estratégias enunciativas em salas de aula de química: contrastando professores de estilos diferentes - Adjane Costa Tourinho e Silva (2008)
In this research, strategies used by two Chemistry teachers in two classrooms on the 2nd high from two different schools were analyzed as well as characterized through a contrasting point of view. The analysis was conducted throughout the thermo-chemistry class sequences. The analyses of such strategies has shown each teachers teaching style considering that such strategies express concepts related to Sciences and its teaching process which conduct both teachers practices in their classrooms. The analyses has also observed how the strategies used in class could provide students with the opportunity of getting involved with the tasks proposed as well as the classroom speech. To analyze those strategies, a category system proposed by Mortimer, Massicame, Tiberghien and Buty was used. Such analytical system is based on Vygotskys and Bakhtins concepts. Some changes in the system had to be made throughout the research, its categories were ordered in two main dimensions: one which focuses the interaction patterns in relation to different functions and types of discourses, and the other one which considers how the content is articulated along the interactions. The second dimension is formed by categories named epistemic. Through this perspective, the strategies shown are related to the interactive and epistemic movements that teachers make use of, interacting themselves with students or not, so as to come up with utterances in the classroom. The concept of Productive Disciplinary Engagement proposed by Engle and Conant was taken into account in order to verify how such strategies could promote learning opportunities for students. Still into the perspective mentioned, the concept of epistemic practices proposed by Kelly was also taken into consideration in a discussion which focused on how the investigated strategies helped to get students involved with the main aspects of Sciences speech. The data was collected through videos, field notes, analyses of students written productions, teachers materials as well as interviews with teachers and students. The methodology included the analyses of data collected through videos in real time using software called Videograph®. The categorization using the Videograph® made it possible to get the time percentage for each category, both each class individually and each class sequence as a whole. This general data was used as a reference for micro analyses through which it was possible to know how the investigated strategies were articulated in both classrooms. The results obtained showed that both teachers were alike when it came to the level of interaction between them and their students. On the other hand, to certain extent, they were reasonable different in relation to dialogic interactions. Such interactions were consistent in the laboratory classes at school A. As for the epistemic categories, it has been observed that the teacher from school A prioritized a strategy, through which the discussions firstly considered specific phenomena, just getting to generalizations afterwards. This epistemic movement, developed along with the laboratory classes inquires, was every time used by the teacher as a way to build new concepts in the classroom. The teacher from school B, however, prioritized an epistemic movement through which concepts or generalizations were firstly made, just applying them in the analyses of specific situations in due time. According to this epistemic movement, the experiments in the laboratory class were discussed so as to demonstrate the concepts previously taught. The obtained results show different strategies which can be used as relevant food for thoughts in graduation courses and study groups for Chemistry teachers. In this research, strategies used by two Chemistry teachers in two classrooms on the 2nd high from two different schools were analyzed as well as characterized through a contrasting point of view. The analysis was conducted throughout the thermo-chemistry class sequences. The analyses of such strategies has shown each teachers teaching style considering that such strategies express concepts related to Sciences and its teaching process which conduct both teachers practices in their classrooms. The analyses has also observed how the strategies used in class could provide students with the opportunity of getting involved with the tasks proposed as well as the classroom speech. To analyze those strategies, a category system proposed by Mortimer, Massicame, Tiberghien and Buty was used. Such analytical system is based on Vygotskys and Bakhtins concepts. Some changes in the system had to be made throughout the research, its categories were ordered in two main dimensions: one which focuses the interaction patterns in relation to different functions and types of discourses, and the other one which considers how the content is articulated along the interactions. The second dimension is formed by categories named epistemic. Through this perspective, the strategies shown are related to the interactive and epistemic movements that teachers make use of, interacting themselves with students or not, so as to come up with utterances in the classroom. The concept of Productive Disciplinary Engagement proposed by Engle and Conant was taken into account in order to verify how such strategies could promote learning opportunities for students. Still into the perspective mentioned, the concept of epistemic practices proposed by Kelly was also taken into consideration in a discussion which focused on how the investigated strategies helped to get students involved with the main aspects of Sciences speech. The data was collected through videos, field notes, analyses of students written productions, teachers materials as well as interviews with teachers and students. The methodology included the analyses of data collected through videos in real time using software called Videograph®. The categorization using the Videograph® made it possible to get the time percentage for each category, both each class individually and each class sequence as a whole. This general data was used as a reference for micro analyses through which it was possible to know how the investigated strategies were articulated in both classrooms. The results obtained showed that both teachers were alike when it came to the level of interaction between them and their students. On the other hand, to certain extent, they were reasonable different in relation to dialogic interactions. Such interactions were consistent in the laboratory classes at school A. As for the epistemic categories, it has been observed that the teacher from school A prioritized a strategy, through which the discussions firstly considered specific phenomena, just getting to generalizations afterwards. This epistemic movement, developed along with the laboratory classes inquires, was every time used by the teacher as a way to build new concepts in the classroom. The teacher from school B, however, prioritized an epistemic movement through which concepts or generalizations were firstly made, just applying them in the analyses of specific situations in due time. According to this epistemic movement, the experiments in the laboratory class were discussed so as to demonstrate the concepts previously taught. The obtained results show different strategies which can be used as relevant food for thoughts in graduation courses and study groups for Chemistry teachers.